Research into the influence of the electromagnetic field on cell ion channels using modeling and measure-ment systems - Rudenko, A.Yu.; Mardzyavko, V.A.; Martynenko, V.O.; Kundenko, M.P. (Radiotekhnika, 2025)
The relevance of the study is due to the growing interest in the regulation of cellular activity under the influence of electromagnetic fields (EMF), which is a promising direction in biomedical engineering. Ion channels, in particular Na⁺, are crucial for maintaining the membrane potential, generating impulses and controlling cell functions. The article proposes the use of computer-aided design systems (CAD) together with control and measurement methods for modeling the influence of EMF on cell ion channels. Mathematical models of ion transport dynamics are presented, in particular the Navier–Stokes equation for describing fluid oscillations, volume transport models and the modified Kuramoto model for studying the synchronization of cellular pulsations. The simulation conducted in MATLAB/Simulink showed that EMF with a frequency of 50 Hz and an amplitude of 100 nA can cause both depolarization (stimulation) and hyperpolarization (inhibition) of the membrane potential depending on the mode of influence. The results demonstrate the possibility of targeted regulation of the permeability of sodium channels, which is confirmed by the data of other studies. The proposed model allows for a deeper understanding of the mechanisms of electrophysiological regulation of the cell and can become the basis for the creation of new methods of therapeutic influence and the development of bioelectronic devices. The results obtained have high practical significance and open up prospects for further experimental and applied research in biomedical technologies.